Психологические аспекты перевода пульмонологических больных с оригинальных препаратов на генерические - А. А. Шабанова (Архивъ внутренней медицины, 2012)
The article deals with one of the very interesting and highly relevant aspects of the treatment of bronchial asthma — the transition from the original drug to generic. Practitioners report that Tevakomb (salmeterol + fluticasone, generic) is sufficiently effective in the primary patients. Meanwhile, in patients treated previously with Seretide (salmeterol + fluticasone, the original drug) when transferred on Tevakomb there may be cases of deterioration. Doctor has to analyse these complaints. Physiologically, it is not understandable because the studies indicate no differences between Tevakomb and Seretide in terms of treatment efficacy in patients with bronchial asthma. Thus, the problem lies in the plane of psychology. The article presents recommendations to doctors, therapists, and respiratory therapists about the least painful transition from more expensive Seretide to cost-effective Tevakomb.